Manajemen Pengelolaan Haceri - Devita Monika; Chairunnisa Aulia; Annisa Alif; Raden Saputra; Farid Fajarullah; Ardi Fidelis; Gustina Rahma; Tri Malinda; Fristy Nur (Lembaga Pengembangan Kinerja Dosen, 2025)
The “Haceri Management” community service program was initiated based on the problems faced by residents, namely cultivation that is still managed individually, limited technical skills in managing feed, and weak capital management and group organization. This activity aims to improve the capabilities of the Haceri community, both technically, socially, and institutionally, so that they can manage their farming businesses more effectively, flexibly, and sustainably. The method used is Participatory Action Research (PAR), in which the community is directly involved as the main actors in every stage, from planning and implementation to evaluation. The series of activities includes technical training in aquaculture, assistance in capital management, facilitation of group discussions, and local leadership development. The results of the activities show an increase in members' ability to manage feed, regulate the breeding process, and perform simple financial record-keeping. From a social perspective, new rules have emerged within the community, a collaborative way of working has developed, and more members are actively participating in group forums. The assistance has also given rise to local leaders who act as motivators and mediators for the community. The shift in attitude towards awareness of the importance of open management and sustainable efforts is an early sign of more inclusive social change. Thus, these activities prove that the success of Haceri management depends not only on improving technical skills, but also on strengthening social cooperation, local leadership, and sustainable community rules.